IMPACT OF BRAND IMAGE, PHYSICAL EVIDENCE, DIGITAL PROMOTION, AND PRODUCT QUALITY ON SALES OF MS GLOW PRODUCTS IN SIDOARJO - Sanggarwati, Diah Ayu; Hermawati, Elok; Kuswandi, Kuswandi (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study examines the effect of brand image, physical evidence, digital promotion, and product quality on sales of MS Glow products in Sidoarjo. This study uses a quantitative method with a descriptive approach. The sample in this study were 55 members of the Dennis Love Shop. This sample was taken using a saturated sampling technique. Data processing using statistical software SPSS 25. The results of the study are as follows, brand image, physical evidence, digital promotion and product quality have a significant effect both partially and simultaneously on sales and in this study product quality has the most significant effect on sales.